Religious coping and the threat of heart transplantation - Sears, Samuel F. (Journal of religion and health, 1994)
The concern of this article is to examine the relationship between religiousness and state-and-trait anxiety in a sample of cardiac transplantation candidates. Religiousness was made operational by integrating measures of religious orientation and religious coping with cluster analysis to form religious coping profiles. Three religious coping profiles were identified:Deferring/Collaborators, Self-Directors, andEclectic. Analyses of variance indicated that coping profiles were significantly different in their report of trait anxiety, such that the Eclectics reported a good deal more trait anxiety than did the Self-Directors. This leads to a discussion of the implications for the clinical presentation of religious coping profiles in cardiac transplantation candidates.